INTERNATIONAL INITIATIVES IN THE FIELD OF TAXATION AND EUROPEAN LAW - Mihaylova-Goleminova, Savina Ivanova (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Abstract Several different initiatives have been developed and implemented in the course of the last few years which modify the elements of familiar taxation systems and principles and are provoked by business globalization, the common European market and trends in the business environment. The present article aims to provide an overview of the G20/OECD’s Base Erosion and Profit Shifting (BEPS) Project – the second major post-financial crisis effort at global cooperation relating to taxation. Another prominent initiative is the global automatic information exchange system, created mainly for the needs of the USA (Foreign Account Tax Compliance Act, i.e. FATCA), as well as the Multilateral Convention on Mutual Administrative Assistance in Tax Matters. The article also discusses current measures of the OECD, the European Union and their transposition in the Bulgarian national legislation.